Impact of Care Bundles Prevention of Hospital‐Acquired Pressure Injuries: A Systematic Review and Meta‐Analysis - Ayse Silanur Demir; Ayise Karadag (Nursing Open)
ABSTRACT Aim To describe and synthesise current literature on care bundles in preventing hospital‐acquired pressure injuries and to present a meta‐analysis of experimental studies evaluating the effects of care bundles. Design A systematic review and meta‐analysis. Methods Pubmed, Cochrane Library, Scopus, Web of Science, CINAHL, Google Scholar and Medline (OVID), and relevant articles were identified from the inception of each database until June 5, 2024. This systematic review has been registered in PROSPERO (CRD42024554497). This study examined a multicomponent intervention care bundles consisting of three or more components that was implemented and compared with standard care. Outcomes were assessed using rates of hospital‐acquired pressure injuries, length of hospital stay (days) and the number of pressure injuries. Study types included randomised controlled trials, nonrandomised studies, quasi‐experimental studies, and cohort studies. After completion of the search, titles, abstracts and full texts were independently assessed by two researchers in consecutive rounds according to PICOS criteria; data were extracted and study quality was independently assessed by at least two researchers. A meta‐analysis using random effects was conducted, where estimates were combined as odds ratios or risk differences, along with proportions and 95% confidence intervals were calculated. Results A total of nine published studies, including 29.572 patients (Control group: 56.8%; Intervention group: 43.2%) were included in this review. The meta‐analysis results showed a significant effect of care bundle intervention on hospital‐acquired pressure injuries rates, length of hospital stay and number of pressure injuries. According to the results of the study, care bundle application reduces the rate of hospital‐acquired pressure injuries, shortens the duration of hospitalisation, and reduces the number and severity of pressure injuries. No Patient or Public Contribution Although patients and the public were not directly involved in the study, the research addresses key concerns about preventing hospital‐acquired pressure injuries. By focusing on care bundles to improve patient safety and reduce pressure injury rates, this study aims to enhance the quality of care, shorten hospital stays and improve patient outcomes, ultimately benefiting both patients and the healthcare system. Trial Registration CRD42024554497